2017
DOI: 10.1080/10615806.2017.1348296
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of peer difficulties to social anxiety in early adolescence: categorical and dimensional analyses with clinical and community samples

Abstract: Our findings supplement recent laboratory-based observational studies on social functioning among adolescents with SAD and other anxiety disorders. Although social anxiety may be associated with unique social skill deficits and impairment, concerns about peer relations should also be considered among adolescents with other anxiety symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 52 publications
2
3
0
Order By: Relevance
“…For example, in Gren-Landell et al [39], socially phobic adolescents showed significantly higher rates of lifetime victimization from peers/siblings than not socially phobic adolescents. This is in line with results of other studies [42,43,44,46,48,49,50,56,58,59,60].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…For example, in Gren-Landell et al [39], socially phobic adolescents showed significantly higher rates of lifetime victimization from peers/siblings than not socially phobic adolescents. This is in line with results of other studies [42,43,44,46,48,49,50,56,58,59,60].…”
Section: Discussionsupporting
confidence: 93%
“…The aim of the cross-sectional quantitative survey by Early et al [56] was to investigate the possible association between social anxiety and other anxiety disorder with peer acceptance or victimization in a clinical sample ( n = 154) compared to a community sample ( n = 116) of adolescents (mean age: 13.07). Results showed that the social anxiety group presented lowest social acceptance compared to other anxiety group and the community sample.…”
Section: Resultsmentioning
confidence: 99%
“…While it was expected that adolescents with SAD symptoms would experience communication difficulties (e.g., de Lijster et al, 2018), GAD symptoms were also related to perceived social impairment. For the boys in this study, the risk associated with GAD was as high as that associated with SAD relative to adolescents with normative levels of anxiety This is consistent with previous findings indicating that adolescents with non-SAD anxiety disorders may show dysfunction in peer relationships, a greater degree of social impairment, and less social acceptance than their healthy peers (Brumariu et al, 2013;Early et al, 2017;Essau et al, 2000). Evidence from neurobiological research showing that neural activity during social interactions…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown that sleep might be a modifiable risk factor in prevention of several mental health problems in adolescence (19,20).…”
Section: Introductionmentioning
confidence: 99%